Dynamic behavior and transformation of technetium species in the Beishan deep geological environment: Implications for high-level radioactive waste disposal - Nan Li; Xianzhe Duan; Kaituo Shi; Wenzhou Xiao; Wenting Bi; Peng Wu; Hafiza Tasneem Nazish; Guowen Peng (Annals of Nuclear Energy, 2027)

Transcriptome and WGCNA analyses reveal NtRAP2-7 activates NtACOH1 expression to enhance low potassium tolerance in tobacco - Hang Lv; Shuang Peng; Dongge Liu; Zhuohan Yang; Yifei Lu; Bi Ren; Liming Lu (Functional & Integrative Genomics, 2026)

The effects of spark plugs and lubricant oils on pre-ignition combustion in a hydrogen fueled engine - An Lu; Peng Yin; Benzheng Fan; Kuicong He; Xiaogang Yang; Yuan Bi; Xiaowei Hao; Yao Li; Huimu Yang; Dong Han (Fuel, 2026)

Effects of Hericium erinaceus powder incorporation on gluten interactions, water-state distribution, starch digestibility and quality characteristics of wheat noodles - Yu-Ling Yang; Chao Yang; Long Yang; Zhang-Jie Bi; Chang-Qing Dong; Xue-Bin Yin; Ze-Xuan Gong; Zhi-Peng Liu; Ke Bian (Food Research International, 2026)

From bisphenol A to its analogues: Shifts in occurrence and risk in wastewater treatment plants - Ke Zhao; Ze-hua Liu; Jian Gong; Bi-qing Li; Peng-jie Huang; Eddy Y. Zeng (Environmental Pollution, 2026)

Construction of SiO2/porous DA-g-C3N4 composite nanofiltration membranes with high Mg2+/Li+ selectivity based on reverse interfacial polymerization - Xin Shi; Qiuyan Bi; Zizhen Peng; Zhicheng Wang; Yakai Lin; Wenzhong Ma; Chuanjie Fang; Chao Zhang; Shiai Xu (Desalination, 2026)

Spontaneous dark transformation of amino acids in microdroplets: An overlooked pathway for atmospheric organic nitrogen cycling - Tao Wang; Hanyao Chang; Yaohao Hu; Xinyu Huang; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

A dual-branch vessel trajectory prediction method integrating AIS and wind-wave-current data under extreme weather conditions - Zhaowei Guo; Fuguo Peng; Xiang Zhang; Haichen Sui; Panpan Zhang; Chunhe Tian; Jinqiang Bi (Ocean Engineering, 2026)

Coffee geographical origin rapid on-site discrimination strategy using an electrochemical fingerprinting platform by optimization of electrolyte concentration and temperature - Chengxiang Yong; Guohua Hui; Zhaoyi Sun; Wenxiong Wu; Yuchen Huang; Huiting Lan; Jianyu Lu; Dianchen Dai; Chengling Xia; Yuqi Xiao; Ying Liao; Zhenjing Su; et al. (Food Chemistry, 2026)

Decoupling interface regulation and L-arginine interface empowerment to construct stable Mg2+/Li+ separation positively charged polyamide nanofiltration membranes - Xin Shi; Qiuyan Bi; Zizhen Peng; Zhicheng Wang; Fangbo Zhu; Yakai Lin; Wenzhong Ma; Chuanjie Fang; Shiai Xu (Chemical Engineering Journal, 2026)

Tailoring subnanometer transport pathways in polyamide nanofiltration membranes for high-permeance Li+/Mg2+ separation - Zhicheng Wang; Xin Shi; Zizhen Peng; Wenzhong Ma; Yakai Lin; Hideto Matsuyama; Qiuyan Bi (Chemical Engineering Journal, 2026)

Alleviating carbon competition between nitrogen and phosphorus removal: dual roles of microaerobic for anammox activation and pre-anaerobic endogenous carbon redirection - Shuangshuang Li; Wei Zeng; Wenzhuo Jiang; Zhaoyang Bi; Xinpeng Wang; Yongzhen Peng (Water Research, 2026)

National environmental health risk assessment of short-term air pollution effects on cardiovascular disease in Australia: A systematic review and meta-analysis - Yannan Li; Peng Bi; Hilary Bambrick; Michael Tong (Environmental Impact Assessment Review, 2026)

Source apportionment of PAEs in surface water using positive matrix factorization combined with dynamic material flow analysis: a case study in the Chongqing section of the Yangtze River, China - Zihan Bi; Linshen Yang; Yueqi Wang; Chao Dong; Siyan Liu; Xuya Peng; Yilu Gu; Xiaofeng Gao (Environmental Impact Assessment Review, 2026)

Caledonian intracontinental metallogeny in South China - Ruizhong Hu; Mingliang Huang; Jiantang Peng; Jiehua Yang; Shanling Fu; Xianwu Bi (Science China Earth Sciences, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Efficient amino acid capture from sludge fermentation by Tetrasphaera enhances simultaneous nitrification, endogenous denitrification and phosphorus removal - Jiayu Zhang; Wei Zeng; Qingan Meng; Qingteng Gong; Yao Lu; Zhaoyang Bi; Yongzhen Peng (Water Research, 2026)

Deep learning-based microfluidic rapid phenotypic AST uncovers early resistance trajectories - Shunji Li; Chenxi Dai; Dongjuan Chen; Chao Wan; Wenhui Wang; Xin Wang; Jingxuan Liu; Ying Zhang; Jinyi Xu; Wei Du; Xiaojun Feng; Yiwei Li; et al. (Science Bulletin, 2026)

Zooplankton as indicators of coastal water quality: a comparative study of PlanktonScope imaging and DNA metabarcoding of seawater and mesh-screened samples - Yingbei Peng; Chun Ming How; Dai Liu; Dumas Deconinck; Mei-Hong Zhao; Jack Chi-Ho Ip; Leo Lai Chan; Hongsheng Bi; Jian-Wen Qiu (Marine Environmental Research, 2026)

A photoinitiated catalytic self-degrading composite material for efficient and stable Cu(II) directional adsorption was constructed based on the bridging synergy strategy - Junyi Song; Jie Hao; Yupeng Wang; Changlong Bi; Chong Peng; Yuanfei Wang; Shuyi Yang; E. Tao (Journal of Hazardous Materials, 2026)

Dietary recommendations and human health risk assessment of PCBs and PBDEs in marine and freshwater products: A case study in Guangdong, China - Linshen Yang; Yutong Xie; Zihan Bi; Xin Liu; Yueqi Wang; Xuya Peng; Jian Sun; Shijun Huang; Mingrong Yue; Xiaofeng Gao; Yilu Gu; Xiaohui Zhu (Journal of Hazardous Materials, 2026)

Chitosan-polyethyleneimine synergistic coating enables pH-responsive adaptive immobilization of sporadically released Cd/Zn in intensive farmland - Xinyao Wang; Gaoyuan Gu; Changlong Bi; Chong Peng; Yuanfei Wang; Yu Zhang; Shuyi Yang; Tao E (Journal of Environmental Management, 2026)

Interatomic push-pull engineering in heterocyclic covalent organic frameworks for boosting photocatalytic hydrogen peroxide production - Wenjun Yang; Jialong Lv; Yuelin Chen; Weikang Peng; Shibin Zheng; Wei Lin; Jinhong Bi; Guocheng Huang (Chemical Engineering Journal, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Dynamic optimization of external carbon dosing in wastewater treatment using seasonally resolved heterotrophic yield coefficients - Peng Xiao; Shanshan Chen; Ning Chen; Qing Huang; Zakhar Maletskyi; Xuejun Bi; Xiaodong Wang (Process Safety and Environmental Protection, 2026)

Recording and monitoring deaths during heatwaves: a scoping review of mortality attribution and surveillance systems - Temesgen Yihunie Akalu; Matthew Anthony Borg; Yohannes Tefera Damtew; Susan L. Heatley; Matt Beaty; Vanessa Prescott; Peng Bi (International Journal of Hygiene and Environmental Health, 2026)

On water intrusion and soil porosity in landslide-induced surge waves: A multi-layer SPH analysis of the Vajont disaster - Zhonghui Bi; Yadong Wang; Hanyun Zhang; Chengwei Zhu; Chong Peng (Computers and Geotechnics, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

Overcoming water limitation in Hippophae rhamnoides: AMF symbiosis optimizes root development and water use efficiency under arid conditions - Chao Wu; Yinli Bi; Suping Peng; Chao Xue; Zengming Ke; Wenbo Zhu; Chuanjiu Zhang (Rhizosphere, 2026)

Fabrication and physicochemical characterization of Litsea cubeba essential oil nanoemulsion/chitosan composite films for yak butter preservation - Qingya Zhang; Yuanyuan Peng; Zhenyu Liu; Meigui Huang; Xiufang Bi; Mehraj Ahmad; Gang Hao (Food Chemistry, 2026)

Two distinct patterns for advanced simultaneous nitrogen and phosphorus removal treating low C/N wastewater in a low DO anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system - Jingwei Ma; Ying Han; Yaning Ji; Hui Sun; Peng Bi; Long Chen; Xinrui Zhang; Xinru Li; Shiquan Ren; Liang Zhu; Qiulai He (Environmental Research, 2026)

Day-night cloud aqueous chemistry diverges organic molecules pathways and health implications - Baichuan Gou; Shuyi Peng; Yaohao Hu; Xiaocong Peng; Wei Sun; Guohua Zhang; Wei Song; Mingjin Tang; Xiaole Pan; Yele Sun; Zifa Wang; Xinming Wang; et al. (Environmental Pollution, 2026)

Highly-selective extraction of lithium from low-quality brines through β-diketone-anchored porous microspheres - Feng Liu; Shimao Xue; Shijie Zhang; Xiaoling Zeng; Peng Zha; Shicong Chen; Sihui Li; Haotian Zhu; Feihu Bi; Liming Yang; Guang Yang; Xubiao Luo; et al. (Chemical Engineering Journal, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Projected seawater inundation induced by land subsidence will weaken the coastal carbon sink effect - Zhixiong Tang; Rongrong Ning; Fubin Luo; Shilei Peng; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; De Wang (CATENA, 2026)

Mutual promotion between waste sludge fermentation and sulfate reduction: Sulfur and carbon metabolism coupling mechanisms - Wenzhuo Jiang; Wei Zeng; Mengjia Zhan; Qingteng Gong; Zhaoyang Bi; Yongzhen Peng (Bioresource Technology, 2026)

Single-particle insights into the initial mixing state of black carbon and polycyclic aromatic hydrocarbons from biomass and coal combustion - Guohua Zhang; Xiaocong Peng; Wei Song; Xinru Huang; Yutong Li; Baoyi Chen; Jianzhong Song; Xinming Wang; Xinhui Bi (Atmospheric Environment, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

A digital microfluidics-based single-cell ddPCR platform for high-throughput gene copy number analysis applied to single cultured cells - Yicheng Sun; Jiancong Liang; Hui Li; Yechen Fan; Te Peng; Siyi Hu; Yuan Gao; Wenli Zhao; Ling Jiang; Khadija Urooj; Hanbin Ma; Mude Shi; et al. (Analytica Chimica Acta, 2026)

Distinct Dispersal Directions Out of the Qinghai–Tibet Plateau Resulted in Contrasting Evolutionary Trajectories - Yuan‐Yuan Ling; Kun‐Li Xiang; Bi‐Bo Zhang; Huan‐Wen Peng; Andrey S. Erst; Liang Zhao; Tatyana V. Erst; Florian Jabbour; Wei Wang (Journal of Biogeography, 2026)
Aim The Qinghai–Tibet Plateau (QTP) harbours high levels of species diversity and endemism, and multiple out‐of‐QTP dispersal routes have been put forward. However, whether different dispersal directions out of the QTP resulted in contrasting evolutionary trajectories remains unknown. Here, we use the sister genera Calathodes and Trollius (Ranunculaceae) as an ideal model to investigate the out‐of‐QTP diversification patterns. Location The Northern Hemisphere. Taxon Calathodes and Trollius (Ranunculaceae). Methods We sampled all four species of Calathodes and 38 species of Trollius to reconstruct a near‐complete species‐level phylogeny based on 12 molecular loci from the nuclear and plastid genomes. Within the phylogenetic framework, divergence times, ancestral ranges and diversification rates were estimated, and ancestral habitat, elevation and climate niche were inferred. Results The most recent common ancestor of Calathodes and Trollius occupied the QTP at ~8 Ma. Calathodes migrated eastward from the QTP to subtropical mainland China at ~4 Ma and then further to Taiwan at ~0.5 Ma. Trollius dispersed into North Asia at ~6 Ma and further reached Northeast Asia, Japan, Taiwan, Europe and North America. Net diversification rates of subtropical Calathodes and North Asian Trollius clades were 0.28 and 0.54 My −1 , respectively. Calathodes and its subtropical clade both prefer the middle‐elevation closed, warm, and humid habitats, while Trollius and its North Asian clade inhabit open, cold, and dry areas. Main Conclusions Calathodes and Trollius both originated in the QTP in the late Miocene and exhibited long‐term habitat and climatic niche conservatism. The distinct out‐of‐QTP dispersal directions in the two genera probably resulted in their subsequent different diversification patterns, associated with the conservatism in habitat‐ and climate‐related niches. Our study suggests the QTP serves as an important source of Northern Hemisphere biodiversity and advances the knowledge of how distinct dispersal directions out of the QTP resulted in contrasting evolutionary trajectories.

Experimental investigation on the dynamic response of approach bridge and wharf structures under vessel collision - Yan Zhu; Cuizhu Zhao; Ming Peng; Qingxin Zhao; Jingchao Bi; Yu Huang (Ocean Engineering, 2026)

Sustainable UV-driven photodegradation of PFOA and HFPO homologs without chemical additives - Yujie Bi; Chengchen Wu; Qianqian Geng; Jixing Peng; Zhijun Tan; Fengling Li; Mengmeng Guo (Journal of Water Process Engineering, 2026)

Distribution pattern of carbon storage by native vegetation in the Yellow River Estuary - Yixuan Wang; Peng Li; Naishuang Bi; Xiao Wu; Houjie Wang (Estuarine, Coastal and Shelf Science, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Combined transcriptome and metabolome analyses reveal that galactose metabolism is vital for tobacco in response to low-nitrate stress - Dong Wang; Yongchang Wen; Haoran Xie; Mingxin Mu; Xianchao Peng; Junju Li; Jixian He; Xiaoli Liu; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (Journal of Genetics, 2026)

Tracing sources and ecological risks: seasonal-spatial variations of potentially toxic element (PTE) pollution in marine sediments of Beibu Gulf - Zihan Bi; Yao Guan; Linshen Yang; Rongtao Ou; Yilu Gu; Huihua Wei; Xin Liu; Zezhuang Liu; Liping Tian; Keyan Xiao; Siyong Quan; Xuya Peng; et al. (Marine Pollution Bulletin, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Influence of filling station model-induced turbulence on hydrogen cloud explosion characteristics and overpressure attenuation behavior - Yifei Liu; Qiuhong Wang; Hu Wen; Zhenmin Luo; Bin Peng; Wei Gao; Zhenbao Li; Mingshu Bi; Siru Wang; Siyuan Wu (Process Safety and Environmental Protection, 2026)

Development of a pH-responsive nanopesticide for efficient delivery of matrine and sustainable control of pine wood nematode - Linxi He; Zhiyi Zhao; Xixiang Xie; Jiahui Chen; Yaoyu Han; Bi Wu; Yang Li; Ling Ma; Jinsong Peng; Chunxia Chen (Pesticide Biochemistry and Physiology, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

Three-dimensional uncertainty analysis of large deformation slope failure considering varied geometry - Zhonghui Bi; Liaojun Zhang; Wei Wu; Hanyun Zhang; Chong Peng (Engineering Geology, 2026)

Simulation and prediction of heavy metal migration using a Monte Carlo-optimized fugacity model in a Yangtze River Delta Industrial Park - Xin Liu; Dong Zhao; Guo Liang; Zihan Bi; Xuya Peng; Yilu Gu; Xiaofeng Gao (Environmental Impact Assessment Review, 2026)

A coupled strain-damage framework for rock deformation and dynamic damage under cyclic loading based on mesoscale elastoplastic elements - Haohao Zhang; Rui Chen; Yazhou Wang; Huijie Bi; Chaojun Fan; Hui Peng (Computers and Geotechnics, 2026)

Convergent enrichment of core functional guilds involved in Fe-N metabolism in anammox and activated sludge: Insights into genome-resolved metagenomics - Hui Sun; Ying Han; Shiquan Ren; Xinrui Zhang; Xinru Li; Peng Bi; Long Chen; Liang Zhu; Guangchao Yang; Jingwei Ma; Qiulai He (Bioresource Technology, 2026)

Occurrence, Distribution and Ecological Risk Assessment of Phthalate Esters in Sediments of Poyang Lake and its Tributaries - Yan Ma; Runxuan Li; Qingyuan Liu; Ke Zhang; Jiale Bi; Bo-Tao Zhang; Yan Liu; Peng Shao (Water, Air, & Soil Pollution, 2026)

Arsenic Inhibits the PA28α/β-PSMB5 Pathway Blocking Phosphorylated TFEB Degradation and Causing Lysosomal Dysfunction that Damages the Liver - Ying Lv; Hongling Wang; Tian Wang; Yue Qin; Dingnian Bi; Haiyan Zhi; Chunyan Du; Jin Peng; Jiaduo Zhang; Yong Hu (Biological Trace Element Research, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

The extracellular polymeric substances and plants drive soil structural reinforcement and water retention in ground fissures - Haining Yu; Yinli Bi; Kaiwei Xu; Suping Peng; Yang Zhou; Yinchu Qiao (Rhizosphere, 2026)

Prediction of overpressure from hydrogen cloud explosions: A study from open space to hydrogen refueling and filling station scenarios - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Jianyi Chen; Hongxiang Wan; Mingshu Bi; Ran Liu; Chaoyuan Hu (Process Safety and Environmental Protection, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Construction of collagen-based gels with slit-like confined structures based on the tanning effect and interlayer reinforcement for Cu(II) selective adsorption from brine - Yupeng Wang; Feng Zhao; Jie Hao; Junyi Song; Chong Peng; Shuyi Yang; Changlong Bi; Tao E (Desalination, 2026)

Dual-function mechanisms of organic acid-modified chitosan composites in hexavalent chromium wastewater remediation - Xueyan Li; Gaoyuan Gu; Changlong Bi; Chong Peng; Shuyi Yang; Tao E (Desalination, 2026)

Metagenomic insights into the survival strategy of Tetrasphaera under prolonged anaerobic conditions: transition from polyphosphate metabolism to fermentation - Zhaoyang Bi; Wei Zeng; Hongjun Liu; Jiayu Zhang; Wenzhuo Jiang; Yongzhen Peng (Chemical Engineering Journal, 2026)

Revealing denitrifying phosphorus removal metabolic diversity and FNA tolerance of Tetrasphaera with nitrate and nitrite as electron acceptors - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Zhaoyang Bi; Yongzhen Peng (Chemical Engineering Journal, 2026)

Combined with wavelet time frequency analysis and lightweight deep convolutional networkintelligent recognition of coal rock acoustic emission signal - Zhong-kai Peng; Wei-jian Liu; Zhi-zeng Zhang; Zhen-xia Yuan; Shi-lei Zhen; Zhuang-zhuang Wang; Xin-bo Luan; Jian-bo Li; Hao-yang Li; Bi-qi Yuan; Shuai Teng; Zi-wei Li (Applied Geophysics, 2026)

Niche differentiation drives microbial community assembly in an anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system: Insights into Anammox self-enrichment - Jingwei Ma; Hui Sun; Yaning Ji; Qiulai He; Long Chen; Ying Han; Peng Bi; Liang Zhu (Water Research, 2026)

Probiotic strain identification and safety assessment of unlabeled bacteria in infant products - Nanlan Wang; Yarong Wu; Yang Liu; Qian Wen; Fan Bai; Yafang Tan; Yujun Cui; Xingyin Liu; Yujing Bi; Ruifu Yang; Peng Luo (International Journal of Food Microbiology, 2026)

Enhanced ciprofloxacin removal from water by chitosan/Mn-modified biochar: Synergistic adsorption at multi-site active centers - Jiangmei Zhao; Shuyi Yang; Changlong Bi; Chong Peng; Yuanfei Wang; E Tao (Desalination, 2026)

Neurodevelopmental toxicity induced by iron oxide nanoparticles: Insights from chick and zebrafish embryonic models - Bi-Xia Huang; Tao Zhang; Qing-Bin Dong; Peng-Xing Lin; Yi Zhou; Xin-Shuo Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Beyond adsorption: Supramolecular bio-gel triggers heavy-metal contaminated soil's self-remediation via electron-cage catalyzed lattice sealing - Gaoyuan Gu; Yan Zhou; Jianing Zhang; Xinyao Wang; Chong Peng; Yuanfei Wang; Changlong Bi; Shuyi Yang; Tao E (Chemical Engineering Journal, 2026)

In situ measurement evidence of selective aqueous-phase formation of ammonium, nitrate, and sulfate in clouds - Ziyong Guo; Guohua Zhang; Xiaocong Peng; Wei Sun; Fengxian Liu; Mei Li; Xiaole Pan; Xinli Du; Jiancheng Wang; Zifa Wang; Xinming Wang; Xinhui Bi (Atmospheric Research, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Isotope tracers reveal plant-soil water dynamics in Shendong mining area: dryland hydrological and ecosystem recovery - Chao Wu; Yinli Bi; Suping Peng; Wenbo Zhu (Rhizosphere, 2025)

The response of non-point source pollution to land use changes based on the SWAT and PLUS models in an agricultural river basin of Yangtze River, China - Yiqing Bi; Depeng Zuo; Yonghui Song; Zongxue Xu; Jing Wang; Dingzhi Peng; Bo Pang; Wenchao Sun; Karim C. Abbaspour; Hong Yang (Journal of Hydrology, 2025)

Alginate-encapsulated calcium-based metal-organic framework for controlled delivery of spirotetramat: A green and efficient strategy - Yaoyu Han; Bi Wu; Linxi He; Chao Xu; Lianxu Shi; Chunxia Chen; Jinsong Peng (Journal of Cleaner Production, 2025)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

Computational simulation assisted exploration of homogenization induced changes in potato protein secondary emulsions for 3D printing - Zhi-gang Huang; Peng-da Ma; Ao-xue Qie; Fei Gao; Chong-hao Bi; Qiu-yue Du (Innovative Food Science & Emerging Technologies, 2025)

Enhancing the antioxidant and barrier properties of carboxymethyl chitosan/polyvinyl alcohol films by incorporating pomelo seed extract nano-emulsion - Zhiwu Huang; Xinrui Tang; Qiang Peng; Qianhua Zhang; Huaicheng Qin; Yongguang Bi; Juan Guo; Fansheng Kong; Haijie Jin; Canzhao Chen; Huiyan Xu (Food and Bioproducts Processing, 2025)

The impact of hydrological regime changes induced by run-of-river hydroelectric stations on fish spawning - Jing Zhang; Wu Sha Ji Pi; Zi Jing Chen; Shi-Tao Peng; Bing Xing; Tao Lan; Er Di A Bi (Ecohydrology & Hydrobiology, 2025)

Tailoring nucleation and crystallization in perovskite solar cells and modules via spatially designed strong coordinating sites - Mengfan Ma; Pengjie Zhang; Peng Mao; Weihui Bi; Jun Lv; Mengyuan Li; Po-Chuan Yang; Zongbao Zhang; Yufei Zhong (Chemical Engineering Journal, 2025)

Microdomain tuning of sulfhydryl-COF in polymer electrolytes enables highly stable solid-state lithium batteries - Linnan Bi; Jiajun Li; Wenxin Peng; Ying Lin; Xiongbang Wei; Sizhe Wang; Jiaxuan Liao (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

The importance of soil depth in determining the impacts of mixed plantations with thinning on soil multifunctionality - Guangqiu Cao; Linli Dai; Jingwen Qiu; Tingting Peng; Yongkang Wang; Jiangchun Liu; Carolina Urbina Malo; Yiquan Ye; Qing-Fang Bi (Plant and Soil, 2025)
Background and aims Mixed plantations are known to enhance ecosystem functions compared to monocultures, yet their effects on microbial community, soil organic carbon (SOC) quality, and soil multifunctionality across soil profiles remain unclear. This study explores how mixed plantation combined with thinning influence both above- and belowground litter inputs, and how these affect the dynamics of SOC, microbial activities, and ultimately, soil multifunctionality in subtropical Chinese fir plantations. Methods We analyzed tree growth and litter inputs, active SOC pools, nutrient dynamics, enzyme activities, microbial communities, and soil properties across soil profiles under three management practices: monoculture, thinning, and mixed plantation combined with thinning. Key drivers of active SOC and soil multifunctionality were identified using random forest and structural equation modeling. Results Mixed plantations with thinning enhanced tree productivity and root biomass, reduced litterfall, and promoted active SOC and soil multifunctionality, especially at intermediate soil depths (20–40 cm). These effects were linked to a lower ratio of oxidoreductase to carbohydrase activities and higher microbial diversity. Soil depth emerged as a dominant factor shaping microbial activity and community composition, with its interaction with soil properties significantly influencing active SOC and soil multifunctionality. Structural equation modeling further revealed that active SOC dynamics were strongly correlated with soil multifunctionality across the soil profile. Conclusions Mixed plantations alleviate depth-related constraints on soil processes, improving the microbial roles in promoting active SOC and soil multifunctionality. These findings highlight the potential of mixed plantations to enhance soil health and ecosystem services, particularly in monoculture-dominated systems.

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

Species- and sex-specific bioaccumulation, tissue-specific distribution, and maternal transfer of per- and polyfluoroalkyl substances in tiger frogs (Hoplobatrachus chinensis) and forest frogs (Rana chensinensis) - Chu-Hong Zhu; Xiao-Jun Luo; Xi Chen; Peng-Peng Chen; Ke Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Research, 2025)

Dual strategies for enhancing anammox predominance in municipal wastewater treatment: micro-granule-driven multi-pathway nitrite supply and enrichment synergy - Shuangshuang Li; Wei Zeng; Wenzhuo Jiang; Zhaoyang Bi; Yongzhen Peng (Chemical Engineering Journal, 2025)

Exploring the mechanism of Cu U cascade adsorption on sodium alginate-based gels: electronic regulation and heteronuclear coordination - Jie Hao; Changlong Bi; Gaoyuan Gu; Shuyi Yang; Chong Peng; Shuang Zhao; Tao E (Chemical Engineering Journal, 2025)

Synergistic A-site engineering and B-site anchoring in photovoltaic perovskites renders efficient and stable solar cells - Runbo Zhao; Weihui Bi; Peng Mao; Jun Lv; Yang Po-Chuan; Mengyuan Li; Pengjie Zhang; Yingying Xu; Shen Xing; Yufei Zhong (Chemical Engineering Journal, 2025)

Integration of partial nitrification, endogenous denitrification and anaerobic ammonia oxidation in low dissolved oxygen anaerobic/oxic/anoxic-aerobic granular sludge reactor treating low carbon to nitrogen ratios wastewater - Jingwei Ma; Long Chen; Yaning Ji; Hui Sun; Ying Han; Liang Zhu; Peng Bi; Qiulai He (Bioresource Technology, 2025)

An overlooked health risk of PM2.5: Elevated respiratory viral susceptibility revealed by assessing inflammatory and antiviral responses to chemical constituents - Shuyi Peng; Juying Lin; Wei Sun; Yaohao Hu; Baichuan Gou; Guohua Zhang; Wei Song; Bin Jiang; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Atmospheric Environment, 2025)

Strengthening test of water treatment performance of foamed fly ash filler based on magnetic modification - T. Xia; Y. Ji; J. Bi; J. Xia; J. Bai; L. Peng; S. Xia (International Journal of Environmental Science and Technology, 2025)

Engineering intermolecular C–F···C=O interactions in covalent organic framework promotes dual-path H2O2 photosynthesis for sustainable disinfection - Yuxin He; Guocheng Huang; Xuejian Guo; Shaokui Chen; Qiaoshan Chen; Wenjun Yang; Weikang Peng; Xiaoying Xu; Jie Ye; Jinhong Bi; Po Keung Wong (Water Research, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Tuning electron transfer pathways on zero-valent iron to boost both reactive species generation and nitrobenzene mineralization - Jianfei Li; Jincan Peng; Chunlei Liu; Yanmeng Bi; Shaopo Wang (Journal of Environmental Chemical Engineering, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Effects of hibernation on the bioaccumulation and tissue distribution of per- and polyfluoroalkyl substances in frogs (Rana tigrina cantor) via skin exposure - Chu-Hong Zhu; Xiao-Jun Luo; Ke-Lan Guan; Jian Guo; Peng-Peng Chen; Xi Chen; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Janus architecture applied in organic photoelectrochemical transistor biosensors for superior selective direction recognition - Shanding Zhou; Peng Ju; Jingtian Chi; Fan Bi; Siyu Wen; Qingjun Feng; Xiaofei Yin; Bingshu Wang (Chemical Engineering Journal, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Advanced low C/N wastewater treatment in an AOA-AGS sequencing batch reactor via aerobically stimulating simultaneous nitrification and denitrification - Jiyi Chen; Long Chen; Yang Liu; Jingwei Ma; Weihong Wu; Xiang Wang; Yaning Ji; Yuhong Wen; Peng Bi; Hui Sun; Ying Han; Xinrui Zhang; et al. (Journal of Water Process Engineering, 2025)

Group activity analysis and pollution remediation techniques: Optimization of gel structural properties for efficient copper adsorption by truncating the electron pooling effect on polymer methylene backbones - Changlong Bi; Suya Li; Gaoyuan Gu; Jie Hao; Yupeng Wang; Chong Peng; Shuyi Yang; Tao E (Journal of Hazardous Materials, 2025)

Edge nucleation and bridging effect synergistically in-situ sealed multiple heavy metals in soils - Gu Gaoyuan; Zhang Jianing; Zhou Yan; Ge Ruijie; Li Wenhui; Peng Chong; Wang Yuanfei; Bi Changlong; Yang Shuyi; E Tao (Journal of Hazardous Materials, 2025)

Electro-cultivation of hydrogen-oxidizing bacteria to promote ammonia resource recovery and microbial protein synthesis in microbial electrolysis cell - Jingwei Ma; Long Chen; Qiulai He; Hui Sun; Ying Han; Liang Zhu; Peng Bi (Chemical Engineering Journal, 2025)

Aluminum ion-activated low-temp pyrolyzed carbon to decontaminate Cr in water and soil - Jianing Zhang; Gaoyuan Gu; Shuyi Yang; Yan Zhou; Jianhua Li; Chong Peng; Yuanfei Wang; Yun Li; Changlong Bi; Tao E (Science of The Total Environment, 2025)

Alginate-collagen fibers composite biomass material for ultra-rapid recovery of strontium from contaminated water with excellent reusability - Liangqiong Peng; Xindi Lv; Yue Sun; Wenhua Zhang; Bi Shi; Jianfei Zhou (Journal of Hazardous Materials, 2025)

Thermodynamic controls on plutonium(Pu) speciation in deep groundwater: Implications for HLW disposal safety at Beishan, China - Nan Li; Xianzhe Duan; Jiale Dou; Wenting Bi; Peng Wu; Nadia Cheemaa; Hafiza Tasneem Nazish; Guowen Peng (Journal of Environmental Radioactivity, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Integration of machine learning and meta-analysis reveals the behaviors and mechanisms of antibiotic adsorption on microplastics - Shuangshuang Bi; Ruoying Wu; Xiang Liu; Peng Wei; Shuling Zhao; Xinru Ma; Enfeng Liu; Hongfeng Chen; Jinling Xu (Journal of Hazardous Materials, 2025)

The dual selective adsorption mechanism on low-concentration Cu(II): Structural confinement and bridging effect - Wenhui Li; Gaoyuan Gu; Changlong Bi; Shuyi Yang; Yuanfei Wang; Chong Peng; Yun Li; Tao E (Journal of Hazardous Materials, 2025)

Mechanism of flavor changes in Northern Pike (Esox lucius) during refrigeration revealed by UHPLC-MS metabolomics and GC-IMS - Shijie Bi; Gao Gong; Na Li; Peng Gao; Tianyu Hou; Jinfang Zhu; Batuer Abulikemu (Food Bioscience, 2025)

Study on the degradation characteristics and strength prediction model of sandstone joints under wetting and drying cycles - Liu He; Jiaxin Yan; Junxiang Bi; Zihai Peng; Liwei Bai (Bulletin of Engineering Geology and the Environment, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

Integrated process of Tetrasphaera-dominated enhanced biological phosphorus removal and sulfur autotrophic denitrification in a single reactor to treat VFAs-free wastewater: Feasibility, performance and mechanism - Hongjun Liu; Wei Zeng; Gangxin Chen; Qingan Meng; Jiayu Zhang; Zhaoyang Bi; Yongzhen Peng (Journal of Water Process Engineering, 2025)

Role of benzothiadiazole in regulating reactive oxygen species and inhibiting cap opening in Agaricus bisporus during storage - Ruirui Yang; Yanan Wei; Hui Peng; Ting Wang; Jianmin Yun; Yan Yin; Yang Bi (Postharvest Biology and Technology, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

High-throughput screening of acetals/ketals in edible essences via GC-Orbitrap-MS and their formation rates at room temperature - Xiaoyu Wang; Qiong Guo; Lining Pan; Cong Nie; Yiming Bi; Yaqiong Qin; Fuwei Xie; Fangqi Du; Yuhan Peng; Bing Wang; Ruihong Liu; Hui Wang; et al. (Food Chemistry, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Biogenic iron mineral formation and the fate of arsenic driven by its coupling with ferrous iron in acid mine drainage environment - Shaozu Xu; Mulin Guo; Caihong Jin; Lixiang Zhou; Jing Shi; Peng Fu; Wenlong Bi; Fenwu Liu (Journal of Hazardous Materials, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Anomalous temperatures increase occupational injuries, illnesses and associated cost burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Urban Climate, 2025)

Aluminum ion catalyzed proton transfer: Mechanism on promoting highly stable passivation of Cr by soil organic matter - Gaoyuan Gu; Jianing Zhang; Yan Zhou; Wenhui Li; Chong Peng; Changlong Bi; Shuyi Yang; Yun Li; E. Tao (Science of The Total Environment, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

A smartphone-assisted ultrasensitive colorimetric aptasensor based on DNA-encoded porous MXene nanozyme for visual detection of okadaic acid - Jingtian Chi; Peng Ju; Fan Bi; Siyu Wen; Zhenbo Xiang; Juna Chen; Meng Qiu (Food Chemistry, 2025)

Inorganic-rich solid electrolyte interphase and oriented (002) crystal plane extension for reversible zinc metal anode - Biyao Du; Jingzhu Chen; Yang Xu; Zhuoran Lv; Peng Ying; Wujie Dong; Luke Yan; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

Angiopoietin-like protein 2 inhibits thrombus formation - Tiantian Zhang; Mingliang Zhang; Lingyu Guo; Dongsheng Liu; Kandi Zhang; Changlong Bi; Peng Zhang; Jin Wang; Yuqi Fan; Qing He; Alex C. Y. Chang; Junfeng Zhang (Molecular and Cellular Biochemistry, 2025)
Acute myocardial infarction is mainly caused by a lack of blood flood in the coronary artery. Angiopoietin-like protein 2 (ANGPTL2) induces platelet activation and thrombus formation in vitro through binding with immunoglobulin-like receptor B, an immunoglobulin superfamily receptor. However, the mechanism by which it regulates platelet function in vivo remains unclear. In this study, we investigated the role of ANGPTL2 during thrombosis in relationship with ST-segment elevation myocardial infarction (STEMI) with spontaneous recanalization (SR). In a cohort of 276 male and female patients, we measured plasma ANGPTL2 protein levels. Using male Angptl2 -knockout and wild-type mice, we examined the inhibitory effect of Angptl2 on thrombosis and platelet activation both in vivo and ex vivo. We found that plasma and platelet ANGPTL2 levels were elevated in patients with STEMI with SR compared to those in non-SR (NSR) patients, and was an independent predictor of SR. Angptl2 deficiency accelerated mesenteric artery thrombosis induced by FeCl 3 in Angptl2 –/– compared to WT animals, promoted platelet granule secretion and aggregation induced by thrombin and collogen while purified ANGPTL2 protein supplementation reversed collagen-induced platelet aggregation. Angptl2 deficiency also increased platelet spreading on immobilized fibrinogen and clot contraction. In collagen-stimulated Angptl2 –/– platelets, Src homology region 2 domain–containing phosphatase (Shp)1-Y564 and Shp2-Y580 phosphorylation were attenuated while Src, Syk, and Phospholipase Cγ2 (PLCγ2) phosphorylation increased. Our results demonstrate that ANGPTL2 negatively regulated thrombus formation by activating ITIM which can suppress ITAM signaling pathway. This new knowledge provides a new perspective for designing future antiplatelet aggregation therapies.

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Characterization and genome analysis of Klebsiella phages with lytic activity against Klebsiella pneumoniae - Shanzheng Bi; Hong Peng; Xiao Wei; Changjun Wang; Xiangna Zhao (Virus Genes, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Molecular characteristics of organic matters in PM2.5 associated with upregulation of respiratory virus infection in vitro - Juying Lin; Wei Sun; Shuyi Peng; Yaohao Hu; Guohua Zhang; Wei Song; Bin Jiang; Yuhong Liao; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Journal of Hazardous Materials, 2025)

Interface-controlled synthesis of nickel phyllosilicate for efficient CO2 hydrogenation to methane: Breaking limitation of the conventional silica-surface-controlled synthesis - Wenhui Bi; Tengfei Zhang; Qing Liu; Yan He; Peng Liang (Fuel, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

Energy, environmental footprints and economic benefit of substituting inorganic fertilizer with organic manure for winter wheat in Huanghuaihai Plain - Lei Wang; Jianjie Bi; Jing Chen; Baizhao Ren; Bin Zhao; Peng Liu; Shubo Gu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

Exploring the mechanism of ursolic acid in preventing liver fibrosis and improving intestinal microbiota based on NOX2/NLRP3 inflammasome signaling pathway - Qi Liu; Lin-Xiang Liu; Bi-Min Li; Wang Zhang; Yue Zhang; Peng Chen; Chen-Kai Huang; Yuan Nie; Xuan Zhu (Chemico-Biological Interactions, 2025)

Biomagnification of polybrominated diphenyl ethers and alternative halogenated flame retardants through food chains of yellowfin tuna (Thunnus albacares) and their prey from the South China Sea and the associated potential health risk - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zhong-Biao Chen; Yue Sun; Jiang-Tao Fan; Jun Zhang; Bi-Xian Mai (Science of The Total Environment, 2024)

Numerical study on wave propagating characteristics through an offshore pile-net enclosure structure - Yun-Peng Zhao; Lian-Xin Xin; Chao Ma; Ke-Zhao Fang; Yi-Xin Li; Chun-Wei Bi (Ocean Engineering, 2024)

Comprehensive comparison of water quality risk and microbial ecology between new and old cast iron pipe distribution systems - Youyi Chen; Huishan Zhou; Hui Gao; Ziliang Su; Xinjun Li; Peng Qi; Tong Li; Chun Hu; Zesong Li; Zhihao Bi; Xueci Xing; Jingxin Yang; et al. (Journal of Environmental Sciences, 2024)

An ultra-high-performance liquid chromatography-quadrupole-orbitrap mass spectrometry based metabolomics investigation on pacific oysters (Crassostrea gigas) during depuration and anhydrous living-preservation - Shijie Bi; Gao Gong; Jinfang Zhu; Peng Gao (Food Bioscience, 2024)

Editorial for Special Issue on “Wind Turbine Structures” - Songye Zhu; Eleni Chatzi; Kaiming Bi; Peng Feng; Jie Yang (Engineering Structures, 2024)

Fine mapping and functional validation of the candidate gene BhGA2ox3 for fruit pedicel length in wax gourd (Benincasa hispida) - Yan Deng; Peng Wang; Wenhui Bai; Zhihao Chen; Zhikui Cheng; Liwen Su; Xianglei Chen; Yeshun Bi; Rongjin Feng; Zhengguo Liu (Theoretical and Applied Genetics, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

In-situ synthesis of 2D nanozymes-coated cellulose nanofibers on paper-based chips for portable detection of biothiols - Chao Di; Yiwei Zhang; Lian Xue; Wenyi Zeng; Tengteng Wang; Yiwei Lin; Peng Chen; Xiaojun Feng; Wei Du; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Scenario analysis of waste tires from China's vehicles future - Di Cui; Zihan Bi; Yao Wang; Yilu Gu; Heming Wang; Xiaofeng Gao; Peng Wang; Xin Sun; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Perfluorooctane sulfonate promotes the migration of colorectal cancer cells by inducing epithelial-mesenchymal transition - Fangfang Li; Lu Chen; Bi-Xia Peng; Yuyang Lei; Minjie Li; Liang-Hong Guo (Journal of Environmental Sciences, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Histidine-derived carbon dots for redox modulation and gut microbiota regulation in inflammatory bowel disease therapy - Jingmin Wang; Haimei Zhu; Zifan Chen; Nannan Peng; Ziyue Liu; Rongjun Sun; Hong Bi; Yongzhong Wang (Chemical Engineering Journal, 2024)

Traditional Chinese medicine formulation ChangQing compound has significant therapeutic effects on chickens infected with Eimeria tenella - Peng Du; Jiajia Yang; Wanjiang Xiang; Ying Chen; Xin Wen; Naixiu Wang; Simei Xian; Bi Wang (Veterinary Parasitology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Hydrodynamics of focused waves acting on netting that extends above the mean sea level - Qiu-Pan Chen; Chao Ma; Yun-Peng Zhao; Chun-Wei Bi; Hang-Fei Liu (Ocean Engineering, 2024)

Research on reliability assessment approach of marine passive safety system based on improved Kriging model and SORM - Yuepeng Bi; Genglei Xia; Chenyang Wang; Minjun Peng; Chang Wang; Chengyan Gu (Annals of Nuclear Energy, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Prediction and comparison of burning rate of n-heptane pool fire in open space based on BPNN and XGBoost - Peng Xu; Yubo Bi; Jian Chen; Shilu Wang; Jihao Shi; Shenshi Huang; Wei Gao; Mingshu Bi (Process Safety and Environmental Protection, 2024)

Machine learning-driven source identification and ecological risk prediction of heavy metal pollution in cultivated soils - Zihan Bi; Jian Sun; Yutong Xie; Yilu Gu; Hongzhen Zhang; Bowen Zheng; Rongtao Ou; Gaoyuan Liu; Lei Li; Xuya Peng; Xiaofeng Gao; Nan Wei (Journal of Hazardous Materials, 2024)

Sustainable forest development in the face of global warming: Optimizing Robinia pseudoacacia L. stands to alleviate soil moisture depletion - Ning Wang; Huaxing Bi; Ruidong Peng; Danyang Zhao; Zehui Liu (Journal of Cleaner Production, 2024)

Regulation of metal utilization ratio and active sites of nickel phyllosilicates for enhanced CO2 methanation - Zeyu Liu; Jia Liu; Hai Li; Peng Xia; Ruixuan Zhu; Wenhui Bi; Qing Liu; Xiuyun Zhang; Peng Liang (Chemical Engineering Journal, 2024)

Carrier gradient core-double shell structure with heterojunction transition layer for significantly enhancing dielectric properties - Peng Wang; Zihao Guo; Zhihao Sun; Guangshen Li; Jingyu Bi; Lei Qian (Chemical Engineering Journal, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

Metal-doped biochar for selective recovery and reuse of phosphate from water: Modification design, removal mechanism, and reutilization strategy - Jianhua Qu; Wei Peng; Mengning Wang; Ke Cui; Jingdong Zhang; Fuxuan Bi; Guangshan Zhang; Qi Hu; Yifan Wang; Ying Zhang (Bioresource Technology, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Identification of odorant-binding proteins in the antennal transcriptome of Cotesia ruficrus and the response of CrufOBP3 and CrufOBP17 to maize volatiles - Wen-Wen Wang; Peng-Yang He; Bi-Ting Tian; Tong-Xian Liu; Xiang-Feng Jing; Shi-Ze Zhang (Journal of Pest Science, 2024)

Duplex Real-Time Fluorescent Quantitative PCR Assays for the Detection of Toxigenic Microcystis Genotypes Based on SNP/InDel Variation in mcy Gene Cluster - Xiangdong Bi; Peng Wei; Qian Wang; Lijin Duan; Wei Dai; Rui Chen; Dajuan Zhang (Current Microbiology, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Synergistic enhancement of regeneration capacity and ecological functions of Robinia pseudoacacia L. plantations in the Loess Plateau - Ning Wang; Huaxing Bi; Ruidong Peng; Danyang Zhao; Zehui Liu (CATENA, 2024)

Insights into the combined toxicity and mechanisms of BDE-47 and PFOA in marine blue mussel: An integrated study at the physiochemical and molecular levels - Qianqian Geng; Liang Zou; Mengmeng Guo; Jixing Peng; Fengling Li; Yujie Bi; Shuqi Jiang; Hanlin Qin; Zhijun Tan (Aquatic Toxicology, 2024)

Immunotoxicity of microplastics in fish - Huiqi Li; Huanpeng Liu; Liuliu Bi; Yinai Liu; Libo Jin; Renyi Peng (Fish & Shellfish Immunology, 2024)

Understanding the links between micro/nanoplastics-induced gut microbes dysbiosis and potential diseases in fish: A review - Yu Cao; Liuliu Bi; Qianqian Chen; Yinai Liu; Haiyang Zhao; Libo Jin; Renyi Peng (Environmental Pollution, 2024)

Uncertainty Analysis of Post-Failure Behavior in Landslides Based on SPH Method and Generalized Geotechnical Random Field Theory - Zhonghui Bi; Wei Wu; Liaojun Zhang; Chong Peng (Computers and Geotechnics, 2024)

Fog/cloud processing of atmospheric aerosols from a single particle perspective: A review of field observations - Guohua Zhang; Xiaocong Peng; Wei Sun; Yuzhen Fu; Yuxiang Yang; Dantong Liu; Zongbo Shi; Mingjin Tang; Xinming Wang; Xinhui Bi (Atmospheric Environment, 2024)

Effects of catechin on the stability of myofibrillar protein-soybean oil emulsion and the adsorbed properties of myosin at the oil–water interface - Guangyao Zhang; Xinxin Bi; Rongrong Wang; Zhiwan Yin; Yue Zheng; Xinyan Peng; Na Jia; Dengyong Liu (Food Chemistry, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

A novel ZIF-L/PEI thin film nanocomposite membrane for removing perfluoroalkyl substances (PFASs) from water: Enhanced retention and high flux - Yujie Bi; Xiangmin Meng; Zhijun Tan; Qianqian Geng; Jixing Peng; Qiaozhi Yong; Xiaojie Sun; Mengmeng Guo; Xinping Wang (Science of The Total Environment, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Development of SV2A Ligands for Epilepsy Treatment: A Review of Levetiracetam, Brivaracetam, and Padsevonil - Peng-Peng Wu; Bi-Rong Cao; Fu-Yun Tian; Zhao-Bing Gao (Neuroscience Bulletin, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Effect of Tetrastigma hemsleyanum leaves and Extract supplementation on liver metabolomics and the gut microbiota in alcohol-induced liver injury - Kexin Tao; Han Peng; Xin Bi; Xiaoya Wang; Yue Tian; Hua Zhang; Yong Sun (Food Bioscience, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effects of ignition position and hydrogen concentration on the flame propagation characteristics of hydrogen–air deflagration - Qiuhong Wang; Hongxiang Wan; Mingshu Bi; Wei Gao; Bin Peng; Zhenmin Luo; Jian Chen; Yunfan Xue (Fuel, 2024)

Characteristics analysis of solid waste generation and carbon emission of beer production in China - Mengqi Fan; Tao Zhou; Ziye Zhao; Yuting Du; Siyan Liu; Zihan Bi; Jiaqi Lu; Hongping He; Lei Li; Xuya Peng; Xiaofeng Gao; Yilu Gu (Environmental Research, 2024)

Mixing state and influence factors controlling diurnal variation of particulate nitrophenol compounds at a suburban area in northern China - Ziyong Guo; Xiaodong Hu; Wei Sun; Xiaocong Peng; Yuzhen Fu; Kun Liu; Fengxian Liu; He Meng; Yujiao Zhu; Guohua Zhang; Xinfeng Wang; Likun Xue; et al. (Environmental Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Steroidal saponins from the roots of Paris verticillata and their anti-proliferative and anti-inflammatory activities - Yan Liu; Yu Bi; Jin-Ting Bai; Si-Yi Wang; Jia-Tong Wu; Yi-Kai Jiang; Peng Jiang; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Conversion mechanism for solving the end-stop problem of hydraulic power take-off system for wave energy - Dahai Zhang; Chenglong Li; Ran Bi; Xin Huang; Zhiwei Sun; Tianlong Lan; Yuankui Wang; Ting Huang; Peng Qian (Ocean Engineering, 2024)

Analysis of forestry management based on dynamic life cycle assessment of biogenic carbon: A case study of a forestry resource-based city in Northeast China - Bo Song; Jin Tang; Feng Long; Yuqing Peng; Fenfen Bi; Yueao Kang; Dayi Qian (Journal of Cleaner Production, 2024)

Understanding the mechanistic roles of microplastics combined with heavy metals in regulating ferroptosis: Adding new paradigms regarding the links with diseases - Qianqian Chen; Yinai Liu; Liuliu Bi; Libo Jin; Renyi Peng (Environmental Research, 2024)

Variation of runoff-sediment relationship at flood event scale in three typical watersheds of the Loess Plateau - Ren Geng; Zixuan Ye; Peng Tian; Qiu Jin; Bo Bi; Guangju Zhao; Xingmin Mu; Tongshun Wang; Dadong Zhu (CATENA, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

An updated review of the genus Rhododendron since 2010: Traditional uses, phytochemistry, and pharmacology - Xing-Jian Liu; Hai-Guo Su; Xing-Rong Peng; Hui-Chang Bi; Ming-Hua Qiu (Phytochemistry, 2024)

Towards environmentally sustainable management: A review on the generation, degradation, and recycling of polypropylene face mask waste - Linxiang Lyu; Monisha Bagchi; Nektaria Markoglou; Chunjiang An; He Peng; Huifang Bi; Xiaohan Yang; Huijuan Sun (Journal of Hazardous Materials, 2024)

Controlled-diffusion centrifugal microfluidic for rapid antibiotic susceptibility testing - Zheng Pang; Shunji Li; Shangang Wang; Zonglin Cai; Shuo Zhang; Chao Wan; Jieqing Wang; Yiwei Li; Peng Chen; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Effects of phytohormone on Chlorella vulgaris grown in wastewater-flue gas: C/N/S fixation, wastewater treatment and metabolome analysis - Wenwen Kong; Shilin Shi; Denghui Peng; Shuo Feng; Lianfei Xu; Xin Wang; Boxiong Shen; Yonghong Bi; Honghong Lyu (Chemosphere, 2023)

New paleoseismic events reveal decamillenial recurrence time for large earthquakes (M ≥ 7) along the Yuguang Graben Fault in North China - Hui Peng; Wenjun Zheng; Shaopeng Dong; Qiyun Lei; Haiyun Bi; Xulong Wang; Dongli Zhang; Xinnan Li; Zhikang Gong; Jinhua Du (Tectonophysics, 2023)

An insight into the benefits of substituting polypropylene with biodegradable polylactic acid face masks for combating environmental emissions - Linxiang Lyu; He Peng; Chunjiang An; Huijuan Sun; Xiaohan Yang; Huifang Bi (Science of The Total Environment, 2023)

Design, modeling and experiments of swing L-shape piezoelectric beam applied to tidal and wave energy harvesting - Bo Feng; Haiyang Xu; Bohan Wang; Yuankui Wang; Yuqin Zhu; Ran Bi; Dahai Zhang; Peng Qian (Ocean Engineering, 2023)

Efficient degradation of ciprofloxacin by a flower-spherical Bi2MoO6/BiOCl Z-type heterojunction photocatalyst enriched with oxygen vacancies - Juanqin Xue; Wen Xiao; Long Shi; Yujie Liu; Peng Wang; Qiang Bi (Journal of Environmental Chemical Engineering, 2023)

Catalytic hydrogenation of lignin-derived aldehydes over bimetallic PdNi/hydrotalcite catalyst under mild conditions - Xingjie Guo; Peng Hong; Lu Yao; Xudong Liu; Zhicheng Jiang; Bi Shi (Fuel, 2023)

Protein modified cellulose nanocrystals on reinforcement and self-driven biodegradation of aliphatic polyester - Siwen Bi; Zhuang Zhang; Zhenzhen Yang; Zitong Shen; Jiahui Cai; Jintao Hu; Haoxiang Jin; Tianhao Qiu; Peng Yu; Bin Tan (Carbohydrate Polymers, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

Facile synthesis of Fe and N co-coped biochar from low temperature pyrolysis of lignin waste for superefficient Th(IV)/U(VI) separation: Performance and mechanism - Lijun Guo; Xiaorong Lai; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Journal of Cleaner Production, 2023)

Sodium nitroprusside alleviates nanoplastics-induced developmental toxicity by suppressing apoptosis, ferroptosis and inflammation - Qianqian Chen; Yu Cao; Huiqi Li; Huanpeng Liu; Yinai Liu; Liuliu Bi; Haiyang Zhao; Libo Jin; Renyi Peng (Journal of Environmental Management, 2023)

Current and projected heatwave-attributable occupational injuries, illnesses, and associated economic burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Environmental Research, 2023)

Towards a better understanding of the anaerobic/oxic/anoxic-aerobic granular sludge process (AOA-AGS) for simultaneous low-strength wastewater treatment and in situ sludge reduction from ambient to winter temperatures - Qiulai He; Xiaohui Yan; Hongyu Wang; Yaning Ji; Jinfeng Li; Liang Liu; Peng Bi; Peng Xu; Baokun Xu; Jingwei Ma (Environmental Research, 2023)

Corrigendum to “Graphitic N-doped biochar for superefficient uranium recycling from nuclear wastewater” [Sci. Total Environ. 882 (2023) 163462] - Lijun Guo; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Science of The Total Environment, 2023)

Numerical study on dynamic analysis of a nine-module floating aquaculture platform under irregular waves - Chao Ma; Yun-Peng Zhao; Chun-Wei Bi; Sida Xie (Ocean Engineering, 2023)

Efficient methotrexate adsorption on magnetic-functionalised UiO-66-NH2: Selectivity, mechanisms and recycling - Qiang Bi; Bo Yang; Kun Zhang; Tong Yang; Peng Wang; Long Shi; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Highly efficient production of monocyclic aromatics from catalytic co-pyrolysis of biomass and plastic with nitrogen-doped activated carbon catalyst - Xiaona Lin; Xiaoyun Chen; Peng Fu; Binbin Tang; Dongmei Bi (Chemical Engineering Journal, 2023)

Advanced low-strength wastewater treatment, side-stream phosphorus recovery, and in situ sludge reduction with aerobic granular sludge - Qiulai He; Xiaohui Yan; Zhiyi Xie; Peng Xu; Zhidong Fu; Jinfeng Li; Liang Liu; Peng Bi; Baokun Xu; Jingwei Ma (Bioresource Technology, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Megacity's pathway toward sustainable food waste management and its environmental performance in a developing country: Evidence from Shanghai, China - Jiefeng Xiao; Tao Tao; Yuqing Shi; Jun Zhao; Bingsi Wu; Jun Tai; Mengqi Xu; Xing Zhang; Yuru Peng; Zhujie Bi; Di Feng; Guangren Qian (Science of The Total Environment, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Performance of anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal system overwhelmingly dominated by Candidatus_Competibacter: Effect of aeration time - Jingwei Ma; Yaning Ji; Zhidong Fu; Xiaohui Yan; Peng Xu; Jinfeng Li; Liang Liu; Peng Bi; Liang Zhu; Baokun Xu; Qiulai He (Bioresource Technology, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Role of Mutations of Mitochondrial Aminoacyl-tRNA Synthetases Genes on Epileptogenesis - Ling-yue Kong; Yi-ze Wu; Run-qi Cheng; Pei-han Wang; Bi-wen Peng (Molecular Neurobiology, 2023)

Heterologous expression of MiMLDP, a major lipid droplet protein of the microalga Myrmecia incisa, in Saccharomyces cerevisiae promotes more triacylglycerol storage principally by enlarging lipid droplet size - Jian-Min Hu; Zheng Sun; Qi-Hui Xu; Xiao-Peng Fang; Yan-Hui Bi; Zhi-Gang Zhou (Algal Research, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Rapid removal and easy separation recovery of Cs+ and Sr2+ by zirconium molybdopyrophosphate-functionalized collagen fibers - Liangqiong Peng; Xin Zhang; Lijun Guo; Jiheng Li; Wenhua Zhang; Bi Shi (Journal of Cleaner Production, 2023)

Graphitic N-doped biochar for superefficient uranium recycling from nuclear wastewater - Lijun Guo; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Science of The Total Environment, 2023)

Hydrodynamic effect of different biofouling types on aquaculture netting - Qiu-Pan Chen; Chun-Wei Bi; Zhi-Xing Zhang; Yun-Peng Zhao (Ocean Engineering, 2023)

Seasonal associations between air pollutants and influenza in 10 cities of southern China - Rui Zhang; Yonghong Li; Peng Bi; Siyuan Wu; Zhibin Peng; Yujie Meng; Yu Wang; Songwang Wang; Yushu Huang; Juan Liang; Jing Wu (International Journal of Hygiene and Environmental Health, 2023)

Intra-urban risk assessment of occupational injuries and illnesses associated with current and projected climate: Evidence from three largest Australian cities - Syeda Hira Fatima; Paul Rothmore; Lynne C. Giles; Peng Bi (Environmental Research, 2023)

Global spatiotemporal trend of satellite-based soil moisture and its influencing factors in the early 21st century - Chenchen Peng; Jiangyuan Zeng; Kun-Shan Chen; Zhen Li; Hongliang Ma; Xiang Zhang; Pengfei Shi; Tiantian Wang; Lu Yi; Haiyun Bi (Remote Sensing of Environment, 2023)

Soy protein isolate-polyguluronate nanoparticles loaded with resveratrol for effective treatment of colitis - Wenhao Li; Decheng Bi; Jiang Yi; Lijun Yao; Jue Cao; Peng Yang; Meiting Li; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Molecular characteristics, sources and transformation of water-insoluble organic matter in cloud water - Wei Sun; Ziyong Guo; Xiaocong Peng; Juying Lin; Yuzhen Fu; Yuxiang Yang; Guohua Zhang; Bin Jiang; Yuhong Liao; Duohong Chen; Xinming Wang; Xinhui Bi (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

TREM2 Inhibits Tau Hyperphosphorylation and Neuronal Apoptosis via the PI3K/Akt/GSK-3β Signaling Pathway In vivo and In vitro - Xiaoqian Peng; Hongsong Guo; Xiao Zhang; Zikang Yang; John Bosco Ruganzu; Zhuoyuan Yang; Xiangyuan Wu; Wei Bi; Shengfeng Ji; Weina Yang (Molecular Neurobiology, 2023)

In-cloud scavenging of chemically segregated particle types by individual particle observation - Yuxiang Yang; Xiaocong Peng; Guohua Zhang; Xiaodong Hu; Ziyong Guo; Wei Sun; Yuzhen Fu; Feng Jiang; Jie Ou; Xiang Ding; Xinming Wang; Xinhui Bi (Applied Geochemistry, 2023)

Systematic optimization of the square arc angle aquaculture tank combining CFD methodology and multi-objective genetic algorithm - Hang-Fei Liu; Xiaozhong Ren; Boru Xue; Chun-Wei Bi; Yun-Peng Zhao; Ying Liu (Aquacultural Engineering, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

Highly efficient U(VI) capture from nuclear wastewater by an easily synthesized lignin-derived biochar: Adsorption performance and mechanism - Lijun Guo; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Environmental Research, 2023)

Prediction of wave force on netting under strong nonlinear wave action - Qiu-Pan Chen; Chun-Wei Bi; Yun-Peng Zhao (Frontiers in Marine Science, 2023)
Under the strong nonlinear wave environment, accurate simulation of wave force for aquaculture netting is an effective guarantee for cage design and safety. In this paper, the horizontal wave forces of a nylon square-mesh netting panel were obtained through a series of strong nonlinear regular wave tests, and their nonlinearity was analyzed by amplitude spectrum. Moreover, the Morison equation based on fifth-order Stokes wave theory was used to reasonably predict the wave force on the netting. The results showed that both wave and wave force have strong nonlinearity, especially the latter. The frequency domain characteristics of the test wave and wave force are similar, while the higher frequency components of the test force are more apparent. The predicted wave forces are in good agreement with the test values in time and frequency domain, and zero or higher frequency components of predicted force are more prominent with the increase of wave steepness. When the range of the Keulegan-Carpenter number is 35-120, the average drag and inertia coefficient of the predicted force are 2.4 and 2.1, respectively. The results can provide a more accurate assessment of the nonlinear wave force on aquaculture facilities.

A methodological framework for assessing pastoral socio-ecological system vulnerability: A case study of Altay Prefecture in Central Asia - Zihan Yang; Bo Li; Bo Nan; Xuhuan Dai; Chenchen Peng; Xu Bi (Science of The Total Environment, 2023)

Metagenomics reveals the increased antibiotics resistome through prokaryote rather than virome after overuse of rare earth element compounds - Alin Song; Jingjing Peng; Zhiyuan Si; Duanyang Xu; Miaomiao Sun; Jiayin Zhang; Sai Wang; Enzhao Wang; Jingjing Bi; Fayao Chong; Fenliang Fan (Science of The Total Environment, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Transient Receptor Potential Vanilloid 4: a Double-Edged Sword in the Central Nervous System - Meng-liu Zeng; Shuo Kong; Tao-xiang Chen; Bi-wen Peng (Molecular Neurobiology, 2023)

Acanthopagrus latus migration patterns and habitat use in Wanshan Islands, Pearl River Estuary, determined using otolith microchemical analysis - Guanglong Tang; Zehua He; Yong Liu; Yayuan Xiao; Sheng Bi; Ye Sun; Jiman Liang; Peng Wu; Teng Wang; Jinyu Ye; Chunhou Li (Frontiers in Marine Science, 2023)
Introduction The waters surrounding the Wanshan Islands are important traditional fishing grounds in China, with rich habitat types. Acanthopagrus latus is an economically important species in this area; however, the distribution of its spawning grounds and habitat use patterns remain unknown. Methods Thus 100 otolith samples of A. latus were collected from three geographic areas (MW: Qi’ao Island Mangrove Water Habitat; OW: Yamen Estuary Oyster Farm Water Habitat; RW: Dong’ao-Guishan Island Reef Water Habitat), and the concentrations of Sr and Ca along the shortest axis of the vertical otolith annual or lunar rings were measured to span the entire life cycle of A. latus , with the core and edge areas corresponding to environmental characteristics at birth and capture, respectively. Results and discussion Analysis of covariance (ANCOVA) revealed that the ratios of Sr/Ca in otolith edges of RW samples are significantly higher than those of OW and MW samples; however, both the values of Sr/Ca ratio in otolith cores collected from OW and MW are comparable with those of RW samples. Cluster analysis and non-metric multidimensional scaling (nMDS) indicated that at the juvenile stage, RW and MW individuals in the two main clusters belonged to the same cluster. There was no significant difference between the cores of the RW samples and the edges of the MW and OW samples. Therefore, the spawning area of A. latus in the Wanshan Islands is thought to have originated from low to medium-salinity waters with mangroves and oyster farm habitats in the Pearl River Estuary. A. latus from RW was found to have three distinct habitat-use patterns: 1) Marine Resident (7.2% of sampled fish) fish that remain in marine habitats for life; 2) Marine Migrant (16.4% of sampled fish) juveniles inhabit low to moderate salinity habitats and migrate to marine habitats as they grow; 3) Estuarine Visitor (76.4% of sampled fish) repeated migration between low to moderate salinity and marine habitats. This suggests widespread migration between estuarine and marine habitats throughout the ontogeny. The plasticity of this habitat use and the protection of spawning grounds should be considered in future fisheries management because A. Latus in this area has been the victim of the overexploitation of resources.

Real-time and accurate detection of citrus in complex scenes based on HPL-YOLOv4 - Lijia Xu; Yihan Wang; Xiaoshi Shi; Zuoliang Tang; Xinyuan Chen; Yuchao Wang; Zhiyong Zou; Peng Huang; Bi Liu; Ning Yang; Zhiwei Lu; Yong He; et al. (Computers and Electronics in Agriculture, 2023)

Antibiotics disrupt lipid metabolism in zebrafish (Danio rerio) larvae and 3T3-L1 preadipocytes - Yuyang Lei; Fangfang Li; Monika Mortimer; Zhi Li; Bi-Xia Peng; Minjie Li; Liang-Hong Guo; Guoqiang Zhuang (Science of The Total Environment, 2023)

Nonlinear dynamics of an aquaculture cage array induced by wave-structure interactions - Haibin Shen; Yun-Peng Zhao; Chun-Wei Bi; Zhijing Xu (Ocean Engineering, 2023)

Simultaneously efficient adsorption and highly selective separation of U(VI) and Th(IV) by surface-functionalized lignin nanoparticles: A novel pH-dependent process - Lijun Guo; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Journal of Hazardous Materials, 2023)

Ultrafast uranium recovery from high-salinity nuclear wastewater using amine-functionalized lignin microspheres - Lijun Guo; Liangqiong Peng; Jiheng Li; Wenhua Zhang; Bi Shi (Journal of Cleaner Production, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

Heatwave and urinary hospital admissions in China: Disease burden and associated economic loss, 2014 to 2019 - Yushu Huang; Hejia Song; Yibin Cheng; Peng Bi; Yonghong Li; Xiaoyuan Yao (Science of The Total Environment, 2023)

Simultaneous removal of Arsenic(III) and Chromium(VI) over ZnFe2O4 {100}/{111} Z-scheme photocatalyst: Facet-dependent active site and overlooked As(III)/Cr(VI) complex - Dashi Lei; Lu Zhang; Huikun Yan; Yuhan Liu; Xiangyu Peng; Wei Xiao; Qiang Bi; Juanqin Xue; Yubin Wang (Journal of Cleaner Production, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “Rapid start-up and stable operation of an aerobic/oxic/anoxic simultaneous nitrification, denitrification, and phosphorus removal reactor with no sludge discharge” [Bioresour. Technol. 362 (2022) 127777] - Qiulai He; Xiaohui Yan; Zhidong Fu; Yihang Zhang; Peng Bi; Xingliang Mo; Peng Xu; Jingwei Ma (Bioresource Technology, 2023)

Sedimentary record of climate change in a high latitude fjord—Kongsfjord - Hang Wu; Binbin Deng; Jinlong Wang; Sheng Zeng; Juan Du; Peng Yu; Qianqian Bi; Jinzhou Du (Acta Oceanologica Sinica, 2023)

Monitoring and molecular mechanism of boscalid resistance of Sclerotinia sclerotiorum in Southwest China - Pengfei Li; Furong Peng; Ruixuan Zhang; Yuheng Yang; Yang Yu; Chaowei Bi (Journal of Plant Diseases and Protection, 2022)

Complete genome sequence of a novel chrysovirus infecting Talaromyces neofusisporus - Yinhui Jiang; Xun Tian; Xiang Liu; Bi Yang; Nianxue Wang; Qinrong Wang; Wenfeng Yu; Xiaolan Qi; Jian Peng; Tom Hsiang (Archives of Virology, 2022)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

High glucose-induced ROS-accumulation in embryo-larval stages of zebrafish leads to mitochondria-mediated apoptosis - Yaoqi Li; Qianqian Chen; Yinai Liu; Liuliu Bi; Libo Jin; Ke Xu; Renyi Peng (Apoptosis, 2022)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Identification of nafamostat mesylate as a selective stimulator of NK cell IFN-γ production via metabolism-related compound library screening - Qinglan Yang; Shuju Zhang; Shuting Wu; Baige Yao; Lili Wang; Yana Li; Hongyan Peng; Minghui Huang; Qinghua Bi; Peiwen Xiong; Liping Li; Yafei Deng; et al. (Immunologic Research, 2022)
Natural killer (NK) cells play important roles in controlling virus-infected and malignant cells. The identification of new molecules that can activate NK cells may effectively improve the antiviral and antitumour activities of these cells. In this study, by using a commercially available metabolism-related compound library, we initially screened the capacity of compounds to activate NK cells by determining the ratio of interferon-gamma (IFN-γ) + NK cells by flow cytometry after the incubation of peripheral blood mononuclear cells (PBMCs) with IL-12 or IL-15 for 18 h. Our data showed that eight compounds (nafamostat mesylate (NM), loganin, fluvastatin sodium, atorvastatin calcium, lovastatin, simvastatin, rosuvastatin calcium, and pitavastatin calcium) and three compounds (NM, elesclomol, and simvastatin) increased the proportions of NK cells and CD3 + T cells that expressed IFN-γ among PBMCs cultured with IL-12 and IL-15, respectively. When incubated with enriched NK cells (purity ≥ 80.0%), only NM enhanced NK cell IFN-γ production in the presence of IL-12 or IL-15. When incubated with purified NK cells (purity ≥ 99.0%), NM promoted NK cell IFN-γ secretion in the presence or absence of IL-18. However, NM showed no effect on NK cell cytotoxicity. Collectively, our study identifies NM as a selective stimulator of IFN-γ production by NK cells, providing a new strategy for the prevention and treatment of infection or cancer in select populations.

Expert consensus on organizing the multidisciplinary team (MDT) diagnosis and treatment of hepato-pancreato-biliary diseases in China - Binhao Zhang; Jian Zhou; Weifen Xie; Kaishan Tao; Shichun Lu; Xianglin Yuan; Lianxin Liu; Weilin Wang; Yilei Mao; Ping Bie; Jingfeng Liu; Xinyu Bi; et al. (Science China Life Sciences, 2022)

Spatial-temporal distributions and influential factors of phthalate acid esters in sediments of three lakes in Inner Mongolia - Yan Ma; Tong Liu; Bo-Tao Zhang; Yan Liu; Peng Shao; Chen Sun; Yichen Zhang; Jiale Bi; Yunkai Dong; Shengrui Wang; Guoming Zhang (Environmental Science and Pollution Research, 2022)

CmPMRl and CmPMrs are responsible for resistance to powdery mildew caused by Podosphaera xanthii race 1 in Melon - Haonan Cui; Chao Fan; Zhuo Ding; Xuezheng Wang; Lili Tang; Yingdong Bi; Feishi Luan; Peng Gao (Theoretical and Applied Genetics, 2022)

Fast CO2 Retrieval Using a Semi-Physical Statistical Model for the High-Resolution Spectrometer on the Fengyun-3D Satellite - Yanmeng Bi; Peng Zhang; Zhongdong Yang; Qian Wang; Xingying Zhang; Chengbao Liu; Pengmei Xu; Lizhou Hou; Junyu Ke; Naiqiang Zhang (Journal of Meteorological Research, 2022)

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Dihydroartemisinin alleviates AngII-induced vascular smooth muscle cell proliferation and inflammatory response by blocking the FTO/NR4A3 axis - Yan-Bing Huo; Xiang Gao; Qi Peng; Qiang Nie; Wei Bi (Inflammation Research, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Vegetation restoration and agricultural management to mitigate nitrogen pollution in the surface waters of the Dan River, China - Wei Wang; Zhanbin Li; Peng Shi; Yan Zhang; Baozhu Pan; Peng Li; Shijie Ding; Jing Li; Zhilei Bi; Xiukang Wang (Environmental Science and Pollution Research, 2021)

Myeloid TBK1 Deficiency Induces Motor Deficits and Axon Degeneration Through Inflammatory Cell Infiltration - Weisong Duan; Le Yi; Yunyun Tian; Huai-peng Huang; Zhongyao Li; Yue Bi; Moran Guo; Yuanyuan Li; Yakun Liu; Yanqin Ma; Xueqin Song; Yaling Liu; et al. (Molecular Neurobiology, 2021)

Detection and significance of exosomal mRNA expression profiles in the cerebrospinal fluid of patients with meningeal carcinomatosis - Peng Cheng; Feifei Feng; Hui Yang; Suqin Jin; Chao Lai; Yun Wang; Jianzhong Bi (Journal of Molecular Neuroscience, 2021)

The impact of land use and socio-economic factors on ammonia nitrogen pollution in Weihe River watershed, China - Zhilei Bi; Yan Zhang; Peng Shi; Xin Zhang; Zexuan Shan; Lijiang Ren (Environmental Science and Pollution Research, 2021)

Effect of temperature and its interactions with relative humidity and rainfall on malaria in a temperate city Suzhou, China - Zhidong Liu; Shuzi Wang; Ying Zhang; Jianjun Xiang; Michael Xiaoliang Tong; Qi Gao; Yiwen Zhang; Shuyue Sun; Qiyong Liu; Baofa Jiang; Peng Bi (Environmental Science and Pollution Research, 2021)

Spatial and temporal characteristics of surface albedo in Badain Jaran Desert, China - Peng He; Lishuai Xu; Rutian Bi; Fan Yang; Zhilei Zhen (Earth Science Informatics, 2021)

A high‐throughput ultrasonic spraying inoculation method promotes colony cultivation of rare microbial species - Xizhi Huang; Pengjie Li; Mengfan Zhou; Yiwei Li; Xiaowen Ou; Peng Chen; Georg Guggenberger; Bi‐Feng Liu (Environmental Microbiology, 2021)
Summary Current method for obtaining microbial colonies still relies on traditional dilution and spreading plate (DSP) procedures, which is labor‐intensive, skill‐dependent, low‐throughput and inevitably causing dilution‐to‐extinction of rare microorganisms. Herein, we proposed a novel ultrasonic spraying inoculation (USI) method that disperses microbial suspensions into millions of aerosols containing single cells, which lately be deposited freely on a gel plate to achieve high‐throughput culturing of colonies. Compared with DSP, USI significantly increased both distributing uniformity and throughput of the colonies on agar plates, improving the minimal colony‐forming abundance of rare Escherichia coli mixed in a lake sample from 1% to 0.01%. Applying this novel USI to a lake sample, 16 cellulose‐degrading colonies were screened out among 4766 colonies on an enlarged 150‐mm‐diameter LB plate. Meanwhile, they could only be occasionally observed when using commonly used DSP procedures. 16S rRNA sequencing further showed that USI increased colony‐forming species from 11 (by DSP) to 23, including seven completely undetectable microorganisms in DSP‐reared communities. In addition to avoidance of dilution‐to‐extinction, operation‐friendly USI efficiently inoculated microbial samples on the agar plate in a high‐throughput and single‐cell form, which eliminated masking or out‐competition from other species in associated groups, thereby improving rare species cultivability.

Quercetin alleviates neonatal hypoxic-ischemic brain injury by inhibiting microglia-derived oxidative stress and TLR4-mediated inflammation - Kai Le; Zhiping Song; Jie Deng; Xin Peng; Jun Zhang; Liang Wang; Lu Zhou; Haidi Bi; Zhengyu Liao; Zhen Feng (Inflammation Research, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

An accurate and efficient radiative transfer model for simulating all-sky images from Fengyun satellite radiometers - Bin Yao; Chao Liu; Shiwen Teng; Lei Bi; Zhiqing Zhang; Peng Zhang; Byung-Ju Sohn (Science China Earth Sciences, 2020)

Shale adsorption characteristics of the Lower Cambrian Niutitang Formation in northern Guizhou based on surface free energy and isosteric heat data - Xijian Li; Liuyu Chen; Peng Pei; Juan Bi (Arabian Journal of Geosciences, 2020)

Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Wu-Shan Dong; Peng-Fei Liu; Yu Liu; Yu Du; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2020)

MPTP-Induced Impairment of Cardiovascular Function - Xiaoli Liu; Bo Wei; Qianqian Bi; Qihang Sun; Li Li; Jian He; Yuancheng Weng; Shenyan Zhang; Genxiang Mao; Yizhong Bao; Shu Wan; Xiao Z. Shen; et al. (Neurotoxicity Research, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Numerical Study on Hydrodynamic Responses of Floating Rope Enclosure in Waves and Currents - Hui Yang; Yun-Peng Zhao; Chun-Wei Bi; Yong Cui (Journal of Marine Science and Engineering, 2020)
Enclosure aquaculture is a healthy and ecological aquaculture pattern developed in recent years to relieve the pressure due to the wild fish stock decline and water pollution. The object of this paper was a floating rope enclosure, which mainly consisted of floaters, mooring lines, sinkers and a net. In order to optimize mooring design factors, the hydrodynamic responses of the floating rope enclosure with different mooring systems in combined wave-current were investigated by experimental and numerical methods. Physical model experiments with a model scale of 1:50 were performed to investigate the hydrodynamic characteristics of a floating rope enclosure with 12 mooring lines. Based on the lumped mass method, the numerical model was established to investigate the effects of mooring design factors on the mooring line tension, force acting on the bottom, and the volume retention of the floating rope enclosure. Through the analysis of numerical and experimental results, it was found that the maximum mooring line tension of the floating rope enclosure occurs on both sides of the windward. Increasing the number of mooring lines on the windward side is helpful to reduce the maximum mooring line tension. Waves and current both have an influence on the mooring line tension; in contrast, currents have a more obvious effect on the mooring line tension than waves. However, the influence of the wave period on the maximum mooring line tension is small. The force endured by the bottom of the floating rope enclosure also changes periodically with the wave period. Yet, the maximum force endured by the bottom of floating rope enclosure occurred at the windward and leeward of the structure. The volume retention of the floating rope enclosure increased with the increasing amount of mooring lines.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Experimental Investigation on Hydrodynamic Coefficients of a Column-Stabilized Fish Cage in Waves - Yun-Peng Zhao; Qiu-Pan Chen; Chun-Wei Bi; Yong Cui (Journal of Marine Science and Engineering, 2019)
This study on hydrodynamic coefficients of a column-stabilized fish cage under wave action plays an important role in the anti-wave design of cages. The regular wave test was used to study the horizontal wave force of the jacket and column-stabilized fish cage under different wave heights, periods, and incident angles; the finite element model of the jacket and the column-stabilized fish cage was established according to the test model. On the basis of the calculation of the finite element model, combined with the wave force obtained from the experiment, the hydrodynamic coefficients of the structure was fitted by the least squares method, and then the drag force, inertial force, and total force of the structure under different conditions were calculated. The results show that the hydrodynamic coefficients of the jacket and netting under the wave condition were more obvious with the change of the KC number and wave incident angles. And as the wave height increased, the drag force, the inertial force, and the proportion of the drag force to the horizontal wave force both increased. When the wavelength was large, the same trend occured as the wave period increased. When the wave incident angles were different, the forces of the jacket and the column-stabilized fish cage were always small in lateral low-frequency waves, which is consistent with the change law of hydrodynamic coefficients of the jacket and netting.

The effects of temperature on human mortality in a Chinese city: burden of disease calculation, attributable risk exploration, and vulnerability identification - Xin Xu; Zuosen Chen; Xiyuan Huo; Chunping Wang; Ning Li; Xianfeng Meng; Qiang Wang; Qiyong Liu; Peng Bi; Jing Li (International Journal of Biometeorology, 2019)

Using the excess heat factor to indicate heatwave-related urinary disease: a case study in Adelaide, South Australia - Matthew Borg; Monika Nitschke; Susan Williams; Stephen McDonald; John Nairn; Peng Bi (International Journal of Biometeorology, 2019)

Effects of background state on tropical cyclone size over the Western North Pacific and Northern Atlantic - Chen Ma; Melinda Peng; Tim Li; Yuan Sun; Jia Liu; Mingyu Bi (Climate Dynamics, 2019)

Heatwave and work-related injuries and illnesses in Adelaide, Australia: a case-crossover analysis using the Excess Heat Factor (EHF) as a universal heatwave index - Blesson M. Varghese; Alana Hansen; Monika Nitschke; John Nairn; Scott Hanson-Easey; Peng Bi; Dino Pisaniello (International Archives of Occupational and Environmental Health, 2019)

Transcriptomic Profiling of Lathyrus sativus L. Metabolism of β-ODAP, a Neuroexcitatory Amino Acid Associated with Neurodegenerative Lower Limb Paralysis - Quanle Xu; Fengjuan Liu; Ruihong Qu; Jason D. Gillman; Chunxiao Bi; Xin Hu; Peng Chen; Hari B. Krishnan (Plant Molecular Biology Reporter, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Regional morbidity and mortality during heatwaves in South Australia - Susan Williams; Kamalesh Venugopal; Monika Nitschke; John Nairn; Robert Fawcett; Chris Beattie; Graeme Wynwood; Peng Bi (International Journal of Biometeorology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Cloning, purification and biochemical characterisation of a GH35 beta-1,3/beta-1,6-galactosidase from the mucin-degrading gut bacterium Akkermansia muciniphila - Bi-Shan Guo; Feng Zheng; Lucy Crouch; Zhi-Peng Cai; Meng Wang; David N. Bolam; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2018)

Mercury isotope constraints on the source for sediment-hosted lead-zinc deposits in the Changdu area, southwestern China - Chunxia Xu; Runsheng Yin; Jiantang Peng; James P. Hurley; Ryan F. Lepak; Jianfeng Gao; Xinbin Feng; Ruizhong Hu; Xianwu Bi (Mineralium Deposita, 2018)

Synthesis and anticonvulsant activity of some novel 7-(benzylamino) -1H-benzo[b][1,4]diazepine-2,4(3H, 5H)-dione derivatives - Yun-Peng Shao; Rong-Bi Han; Hui-Fan Wu; Feng-Yu Piao (Medicinal Chemistry Research, 2018)

Overexpression of the transcription factor NF-YC9 confers abscisic acid hypersensitivity in Arabidopsis - Chao Bi; Yu Ma; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2017)

Heat adaptation and place: experiences in South Australian rural communities - Susan Williams; Scott Hanson-Easey; Guy Robinson; Dino Pisaniello; Jonathan Newbury; Arthur Saniotis; Peng Bi (Regional Environmental Change, 2017)

Risk factors for deaths during the 2009 heat wave in Adelaide, Australia: a matched case-control study - Ying Zhang; Monika Nitschke; Antoinette Krackowizer; Keith Dear; Dino Pisaniello; Philip Weinstein; Graeme Tucker; Sepehr Shakib; Peng Bi (International Journal of Biometeorology, 2017)

Removal of polybrominated diphenyl ethers by biomass carbon-supported nanoscale zerovalent iron particles: influencing factors, kinetics, and mechanism - Rongbing Fu; Zhen Xu; Lin Peng; Dongsu Bi (Environmental Science and Pollution Research, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Overexpression of an MYB-Related Gene FvMYB1 from Fraxinus velutina Increases Tolerance to Salt Stress in Transgenic Tobacco - Tian Li; Jingkuan Sun; Yuping Bi; Zhenying Peng (Journal of Plant Growth Regulation, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Overexpression of the MYB transcription factor MYB28 or MYB99 confers hypersensitivity to abscisic acid in arabidopsis - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Biology, 2016)

Depth profile of persistent and emerging organic pollutants upstream of the Three Gorges Dam gathered in 2012/2013 - Dominik Deyerling; Jingxian Wang; Yonghong Bi; Chengrong Peng; Gerd Pfister; Bernhard Henkelmann; Karl–Werner Schramm (Environmental Science and Pollution Research, 2016)

Two-dimensional inversion of spectral induced polarization data using MPI parallel algorithm in data space - Zhi-Yong Zhang; Han-Dong Tan; Kun-Peng Wang; Chang-Hong Lin; Bin Zhang; Mao-Bi Xie (Applied Geophysics, 2016)

Overexpression of the MYB37 transcription factor enhances abscisic acid sensitivity, and improves both drought tolerance and seed productivity in Arabidopsis thaliana - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2016)

Narciclasine, a potential allelochemical, affects subcellular trafficking of auxin transporter proteins and actin cytoskeleton dynamics in Arabidopsis roots - Yanfeng Hu; Xiaofan Na; Jiaolong Li; Lijing Yang; Jia You; Xiaolei Liang; Jianfeng Wang; Liang Peng; Yurong Bi (Planta, 2015)

Cardioprotective Effect of Anisodamine Against Myocardial Ischemia Injury and its Influence on Cardiomyocytes Apoptosis - Kun Xing; Xianghua Fu; Lingling Jiang; Yanbo Wang; Wei Li; Xinshun Gu; Guozhen Hao; Qing Miao; Xiaolin Ge; Yuhong Peng; Wei Geng; Shiru Bai; et al. (Cell Biochemistry and Biophysics, 2015)

Erratum to: Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

Dysfunction of hippocampal interneurons in epilepsy - Yu-Qiang Liu; Fang Yu; Wan-Hong Liu; Xiao-Hua He; Bi-Wen Peng (Neuroscience Bulletin, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Engaging stakeholders in an adaptation process: governance and institutional arrangements in heat-health policy development in Adelaide, Australia - Derick A. Akompab; Peng Bi; Susan Williams; Arthur Saniotis; Iain A. Walker; Martha Augoustinos (Mitigation and Adaptation Strategies for Global Change, 2013)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Infrared microthermometric and stable isotopic study of fluid inclusions in wolframite at the Xihuashan tungsten deposit, Jiangxi province, China - Wenfeng Wei; Ruizhong Hu; Xianwu Bi; Jiantang Peng; Wenchao Su; Shengqiong Song; Shaohua Shi (Mineralium Deposita, 2012)

IL-1β: an important cytokine associated with febrile seizures? - Hong-Mei Yu; Wan-Hong Liu; Xiao-Hua He; Bi-Wen Peng (Neuroscience Bulletin, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Molecular characterization of two sweepoviruses from China and evaluation of the infectivity of cloned SPLCV-JS in Nicotiana benthamiana - Huiping Bi; Peng Zhang (Archives of Virology, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Pseudoxanthomonas jiangsuensis sp. Nov., a DDT-Degrading Bacterium Isolated from a Long-Term DDT-Polluted Soil - Guang-li Wang; Meng Bi; Bin Liang; Jian-dong Jiang; Shun-peng Li (Current Microbiology, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Proteomic analysis of cell lines to identify the irinotecan resistance proteins - Xing-Chen Peng; Feng-Ming Gong; Meng Wei; Xi Chen; Ye Chen; Ke Cheng; Feng Gao; Feng Xu; Feng Bi; Ji-Yan Liu (Journal of Biosciences, 2010)

A method for generating precise gene deletions and insertions in Escherichia coli - Qi-Ming Zhou; Dong-Jie Fan; Jiang-Bi Xie; Chuan-Peng Liu; Jun-Mei Zhou (World Journal of Microbiology and Biotechnology, 2010)

Crystallisation conditions (T, P, fO2) from mineral chemistry of Cu- and Au-mineralised alkaline intrusions in the Red River–Jinshajiang alkaline igneous belt, western Yunnan Province, China - Bi Xianwu; Hu Ruizhong; J. J. Hanley; J. E. Mungall; Peng Jiantang; Shang Linbo; Wu Kaixing; Suang Yan; Li Hongli; Hu Xiaoyan (Mineralogy and Petrology, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Optimizing the shoot proliferation protocol of Penthorum chinense by axillary buds - Li-Qiang Wang; Jun Yang; E. Deng; Guang-Bi Wang; Zheng-Song Peng (Biotechnology Letters, 2008)

Effects of Chromium Picolinate on Oxidative Damage in Primary Piglet Hepatocytes - Gao-Yi Tan; Jin-Ming Bi; Min-Hong Zhang; Jing-Hai Feng; Peng Xie; Shan-Shan Zheng (Biological Trace Element Research, 2008)

Study of Oxidative Damage in Growing–Finishing Pigs with Continuous Excess Dietary Chromium Picolinate Intake - Gao-Yi Tan; Shan-Shan Zheng; Min-Hong Zhang; Jing-Hai Feng; Peng Xie; Jin-Ming Bi (Biological Trace Element Research, 2008)

Climate variations and salmonellosis transmission in Adelaide, South Australia: a comparison between regression models - Ying Zhang; Peng Bi; Janet Hiller (International Journal of Biometeorology, 2008)

Co-expressing GP5 and M proteins under different promoters in recombinant modified vaccinia virus ankara (rMVA)-based vaccine vector enhanced the humoral and cellular immune responses of porcine reproductive and respiratory syndrome virus (PRRSV) - Qisheng Zheng; Desheng Chen; Peng Li; Zhixiang Bi; Ruibing Cao; Bin Zhou; Puyan Chen (Virus Genes, 2007)

Genome-wide analysis of Arabidopsis responsive transcriptome to nitrogen limitation and its regulation by the ubiquitin ligase gene NLA - Mingsheng Peng; Yong-Mei Bi; Tong Zhu; Steven J. Rothstein (Plant Molecular Biology, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Precise molybdenite Re–Os and mica Ar–Ar dating of the Mesozoic Yaogangxian tungsten deposit, central Nanling district, South China - Jiantang Peng; Mei-Fu Zhou; Ruizhong Hu; Nengping Shen; Shunda Yuan; Xianwu Bi; Andao Du; Wenjun Qu (Mineralium Deposita, 2006)

Relationships among multiple trace elements in coastal Casuarina equisetifolia ecosystems on Hainan Island, South China - Qiang Liu; Hua Bi; Lan Hung; Shaolin Peng; Chengde Sheng (Environmental Geochemistry and Health, 2006)

Effect of erythromycin on metabolism of quetiapine in Chinese suffering from schizophrenia - Kun-Yan Li; Xin Li; Ze-Neng Cheng; Bi-Kui Zhang; Wen-Xing Peng; Huan-De Li (European Journal of Clinical Pharmacology, 2005)

Fluorescence Enhancement and Photostability of Novel Pentamethine Cyanines in Nafion-Na+ Membranes - Jing-Qu Guan; Zhi-Fei Dai; Chen-Ho Tung; Bi-Xian Peng (Journal of Fluorescence, 2000)